Efektivitas Kombinasi Ekstrak Daun Zodia (Evodia suaveolens) dan Kulit Jeruk Siam (Citrus Sinensis) Sebagai Larvasida Nyamuk Aedes aegypti - Najya Zuhdi (Fakultas Kedokteran, 2025)
The continuous use of chemical larvicides (temephos) to control dengue vectors can lead to the formation of resistance in Aedes aegypti larvae and cause negative impacts on the environment. Zodia leaf and siamese orange peel have potential as natural larvicides because they contain toxic compounds to larvae. There is currently no research on the combination of both extracts as larvicides. The combination of both extracts is expected to enhance the effectiveness in killing Aedes aegypti larvae. This study aimed to determine the larvicidal efficacy of the combination of zodia leaf and siamese orange peel extract against Aedes aegypti mosquito larvae. Methods: This form of research is a true experimental study with a Completely Randomized Design. This study involved two stages of larvicide tests: preliminary tests and larvicide tests of extract combinations. There were five groups of combinations P1 (0:1), P2 (1:0), P3 (0.25:0.75), P4 (0.5:0.5), P5 (0.75:0.25) and two control groups (positive temephos 1% and negative). Each group consisted of 25 Aedes aegypti larvae instar III and IV with 4 replications. The number of larval mortality were observed after 3, 12, 18, and 24 hours. Results: All groups of combinations of zodia leaf and siamese orange peel extracts showed a 100% mortality percentage in 24 hours with a 𝐿𝑇50 value of 6.933 hours. Mann-Whitney test results showed no significant difference in the number of larval mortality in the extract combination group with temephos 1% or between extract combination groups. Conclusion: This study concludes that the combinations of zodia leaf and siamese orange peel extracts are effective as a larvicide against Aedes aegypti mosquito larvae. The combination group of zodia leaf extract (0.375%) and siamese orange peel extract (0.5%) with a ratio of 0.5:0.5 was the most effective combination in causing mortality of Aedes aegypti within 12 hours.
Reupload file repository 16 Maret 2026_Ratna
Keywords: Combined larvicide; zodia leaf; siam orange peel; Aedes aegypti larvae.